Comparing the Use of Scientific Software and Generative AI Art Tools: Exploratory research and future agenda - Francisco Queiroz (Inmaterial, 2025)
The introduction of Generative Artificial Intelligence (GenAI) image and text generators has brought a renewed and significant amount of attention to textual user interfaces. Platforms such as ChatGPT and Midjourney generate, respectively, text and images from verbal instructions typed by users in natural language and processed by Machine Learning models. The use of natural language in GenAI differs from scientific software use interfaces, usually operated through programming and scripting languages. Still, both computational science and generative art, in their own ways, replace traditional ‘wet’ processes with abstract, dematerialised ones.